Analysis and Structural Optimization of Gearbox for New Type Lightweight Bridge Crane - Zhu Shuaihua; Wang Zhengbing; Zhang Zhihong; Yan Shidang; Liu Zhongming (Jixie chuandong)
Reducer is the key component of hoisting equipment,and the case is the carrier of the gear system and plays the role of support and fixation. The three-dimensional finite element model of the gearbox is established by Solid Works software and imported it into ANSYS Workbench. The statics analysis is accomplished for each actual loading condition,the changing curve of the maximum stress and the deformation is obtained,the analysis results can provide the data support for the subsequent structure improvement and light-weight design. The natural frequency and vibration type is obtained by completing the modal analysis of the case,and whether the resonance phenomenon happens can be determined by comparing the natural frequency of the reducer with the meshing frequency and the rotational frequency.